Molecular identification of Paragonimus heterotremus Chen et Hsia, 1964 in Vietnam - Hoa, Le Thanh; Nga, Nguyen Bich; De, Nguyen Van; Cong, Le Dinh; The, Dang Tat (Academia Journal of Biology, 2015)
A region of 376 nucleotides of the mitochondrial-encoded cox1 gene from 6 samples of Paragonimus sp. collected in the Laichau and Sonla provinces was amplified by polymerase chain reaction (PCR) and comparatively aligned with the known corresponding sequences of Paragonimus heterotremus (geographical origin of China and Thailand) and representative species of the Paragonimus genus (GenBank and published data). Molecular-based analysis revealed that Paragonimus sp. of Vietnam is Paragonimus heterotremus Chen et Hsia, 1964, showing high nucleotide similarity to that of China and Thailand strains (over 99%). Phylogenetic analysis uniquely groups the Paragonimus sp. of Vietnam with the Paragonimus heterotremus of China and Thailand.